Simulação de circuitos digitais com aplicação em placa arduino - Cunha, Raone Victor da (Universidade Federal Rural do Semi-Árido, 2018)
With advances in technology, digital systems are developing very fast. The variety of digital materials that exist today can be components, making systems increasingly complex. The most precious, most analyzed and accurate need to be taken. For this reason, a widely used method is the development of simulators. To improve the creation of digital modules with the use of simulators, especially in the educational environment, it is necessary a simulator development solution that is applied to an Arduino board, allowing a great physical demand for major developments for the circuit. To develop the applied simulator, the Arduino was created by a simple language that describes the system that will be simulated. This description will be used, via a transpiler, to generate a C-language code of the described circuit. This code was created by the transpiler to be compiled into an Arduino, enabling a physical experience. Checking the results of the simulations and comparing with the truth table generated by a digital simulator, I realized that language development was one of the most sought after, where the circuit simulated on the Arduino board behaved like the circuit initially described.
Monografia
Keywords: Circuitos Digitais; Linguagem C; Transpilador; Simulador; Arduino; Digital Circuits; Language C; Transpiler; Simulator; Arduino; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA